ผลของนวัตกรรมหนากากพนยาแสนสนุกรวมกับการมีสวนรวมของผูปกครองตอความกลัวของผูปวยเด็กวัยกอนเรียน The Effect of Fun Nebulizer Innovation with Parents Participation on Fear Among Preschool Patients Receiving Aerosol Therapy. - ภูนากลม เนตฤทัย; เรืองบริบูรณ์ สมสมร (วารสารพยาบาลศาสตร์และสุขภาพ, 2014)
This quasi-experimental research aimed to study the effects of fun nebulizer innovation with parent participation on fear among preschool patients receiving aerosol therapy. The sample were 30 preschool patients age from 3 to 6 years old, divided into experimental and control groups with 15 children in each group. The ex-perimental group received the innovation whereas the control group received routine nursing care. The research instruments included : 1) The fun nebulizer innovation with parent participation literature 2) Fear face scale, the reliability of the scale by test-retest with the pearson’s correlation coefficient was 1, and 3) Fear behavior observing scale, the reliability of the scale by cronbach’s coefficient was 0.90. The data were analyzed by using descriptive statistics and independent-sample t-test. The results of this study showed the experimental group reported significantly less fear face scores and fear behavior scores than the control group (p < 0.05).